Novel natural myricetin with AIE and ESIPT characteristics for selective detection and imaging of superoxide anions in vitro and in vivo. Issue 73 (23rd August 2019) - Long, Ruiqing; Tang, Cui; Xu, Jinju; Li, Te; Tong, Chaoying; Guo, Ying; Shi, Shuyun; Wang, Daijie
Abstract : A novel reversible AIE + ESIPT probe, myricetin, easily obtained from vine tea, for detection and imaging of O2 − . Abstract : A novel AIE probe with ESIPT characteristics, myricetin, has been easily purified from vine tea for reversible, selective and sensitive targeting of O2 ˙ − in turn-on mode. Its AIE nanocrystals exhibit large Stokes shift, high photostability, excellent biocompatibility, and low cytotoxicity for endogenous O2 ˙ − detection and imaging in vitro and in vivo .